Rhetorical structure in the problem statement section of Iranian postgraduate students' research projects - Tarvirdizadeh, Zahra (2018)
One of the criteria that can influence the quality of postgraduate students’ academic writing is the way they organize their ideas in their research projects and theses. Among the various parts of a thesis, the Problem Statement (PS) is the most important part as it presents the initial reason why the research project should be conducted. This study focuses on the structure of the PS, since it has rarely been considered as an independent section in earlier research. Swales’ (1990) Create-A-Research-Space (CARS) model was used to analyze the PS sections written by Iranian postgraduate students. In this regard, based on Pho’s (2013) classification, the specific types of linguistic features associated with each move and step were identified besides exploring their writers’ perceptions of the content and the organization of a proper PS. To meet these objectives, 30 MA research projects were collected from purposively selected Iranian postgraduate students. The students who had written these were PhD students in two different universities in Iran while this study was in progress. Move analysis was used to analyze the rhetorical moves of the PS sections of the research projects. Following Pho (2013), the linguistic features as important signals of moves were identified. Thematic analysis of the interviews indicated the students’ perceptions. The findings showed that the rhetorical structures of the PS sections of the Iranian EFL postgraduate students included the expected moves and all moves, and their respective steps were identified linguistically in all the samples although their sequence and arrangement were not the same as what is expected in the model. The obligatory moves were M1’Establishing a Territory’ and M2 ‘Establishing a Niche’. The results demonstrated that the writers of the PSs were more concerned with M1’Establishing a Territory’ rather than M2 ’Establishing a Niche’. Although, the cyclic and embedded moves were defined in the rhetorical structure of the PSs but most of them were anomalous or ill-structured. In contrast, the results of the thematic analysis showed that the students have misconceptions toward the content and organization of the PS section. The results help the understanding of the nature and function of this genre and can have important implications for EFL instructors. The study has theoretical contributions, the most significant one of which is that the CARS model is applicable to define and analyze the rhetorical structure of PSs even though originally it was developed for the purpose of analyzing the whole introduction section.